Références violentes et toponymie des quartiers à Tokombéré - Gigla Garakcheme (Sociétés et Jeunesses en Difficulté)
This contribution articulates on the modes of space appropriation and modes of social expression of youths in a social and economic crisis context in the small town of Tokombere in the North of Cameroon. The new names of quarters given by the youths are henceforth like pertinent sites with territorial marks showing a new social dynamics. In other words the goal is to bring out the oblique modes of affirmation of oneself or the adaptation in a period of crisis in the neotoponymy of the quarters. These results come from a field study that consisted of observation and discussions carried out between November 2005 and May 2006.